Influência da superposição de microindentações em material frágil modelo para estudo de fundamentos de abrasão - Teles, Vinícius Carvalho (2018)
Subsurface cracks, also called lateral cracks, are commonly related to the abrasive wear process on materials with brittle characteristics. These cracks are generally observed in instrumented indentation experiments with loads above critical. However, previous results have shown that the interaction between indentations, even at low loads, can lead to lateral cracks. In this work, the superimposition of microindentations in soda-lime glass, a typically brittle material, was studied using computational simulation and experimental techniques. The tests consisted of seven indentation lines with five indentations in each row. The relative distance of the indentations was changed on each line, controlling the values of the superimposition index from -200% to 90%. To evaluate the effect of the indenter shape, two square and one triangular indenter were used. The Concrete Damage Plasticity (CDP) module, already implemented at Abaqus, was used to simulate the fracture during indentation, taking into account the tensile damage and the plasticity under compression. The numerical model was validated using instrumented indentations tests. For a higher superimposition index, a change in the strength of the material was observed and, consequently, a greater force was required to reach the same indentation depth. As expected, the shape of the indenter affected the tensile field around the indentation and the surface damage. A single indentation with a load below the critical does not cause a stress high enough to induce a lateral crack. However, with the increase of the superimposition index, the interaction of the stresses near the last indentation induced a lateral crack, in loads under the critical value. The position and depth of the stress spot changed according to the shape of the indenter and the indentation depth. The results of the simulation were in agreement with the experimental tests. It was possible to observe the mechanics of lateral crack formation using the stress distribution obtained in the simulation tests. The crack formation was directly related to the superposition index and to the shape of the indenter. The results brought new insight into the predominant wear mechanism and a new model to represent abrasion in brittle materials.